(untitled) - Wolter, Romanus (New Jersey, 2006)
Let "The Kick Start Guy", who inspires 2.4 million entrepreneurs monthly, introduce you to a profound four-step process for achieving important goals in your life and work. Gain the discipline, skill, and mastery it takes to pursue your purpose in life. This practical, life-affirming guide gives you the tools and techniques you need to create conversations that inspire others to help you succeed.
Keywords: Success,Success in business,Attitude (Psychology),Sự thành công,Thành công trong kinh doanh,Thái độ (Tâm lý); Psychological aspects,Khía cạnh tâm lý